The effect of off-season training programming for Edmonton rowers: The effect of pulmonary muscle training on rowing performance - Bell, G.; Syrotiouk, D.; Game, A.; Jones, R. L. (2004)
There was a significant increase in VO2max, bench and leg press mRM strength levels, as well as a significant decrease in 2000 m rowing time after training. There were no significant differences between the chest muscle training group and sham placebo group on any of these dependent measurements. There was a significant increase in resting PE and PI pressure in the chest muscle-training group. The increase in PE pressure was significantly higher than the sham placebo group after training. PE pressure during recovery from maximal exercise was higher than before training in both groups. Recovery PI pressure as higher after training with chest muscle training and when compared to the sham placebo group. Perceived respiratory effort during the 2000 m test was less after chest muscle training only. There were no significant changes in forced vital capacity after training in either group.